2006
DOI: 10.1007/s10404-006-0107-6
|View full text |Cite
|
Sign up to set email alerts
|

All-angle removal of CO2 bubbles from the anode microchannels of a micro fuel cell by lattice-Boltzmann simulation

Abstract: The removal of carbon dioxide (CO 2 ) at the anode of a micro direct methanol fuel cell (lDMFC) is critical. The bubbles are generated at the anode and may block part of the catalyst/diffusion layer, causing the lDMFC to malfunction. This work discusses the CO 2 bubble dynamics of microfluidics in a lDMFC from a microscopic perspective. A two-dimensional, nine-velocity lattice-Boltzmann model was adopted in this work to simulate the two-component (CO 2 bubble plus methanol solution) two-phase (gaseous and liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Fei, K. and C.W. Hong, 2006 99 simulated the effect of inclination angle on microchannel fuel cell system. They reported that the change of inclination angle has a direct effect on bubbles velocity inside the cell.…”
Section: Bubbles Management By Cell Componentsmentioning
confidence: 99%
“…Fei, K. and C.W. Hong, 2006 99 simulated the effect of inclination angle on microchannel fuel cell system. They reported that the change of inclination angle has a direct effect on bubbles velocity inside the cell.…”
Section: Bubbles Management By Cell Componentsmentioning
confidence: 99%
“…Together with the liquid methanol-water solution a two-phase flow forms which exhibits a slug/intermittent flow pattern for most current densities of interest. Fei et al (2006) and Fei and Hong (2007) investigated the bubble transport in a micronsized channel by a 2D LB method. In a follow-up paper, they studied heat transfer including Marangoni effects due to a temperature dependent surface tension and found that bubbles moved more rapidly in a divergent microchannel than in a straight or convergent channel (Fei et al 2008).…”
Section: Marangoni Effects and Surfactantsmentioning
confidence: 99%
“…We constructed mathematical models using a thermal lattice-Boltzmann method (TLBM) to observe the phenomenon of CO 2 bubbles in the anode microchannel of a lDMFC. The main focus of this research is on the thermal and geometric effects of the microchannel flow from a microfluidic viewpoint, the hydrophilic effect was inherited from the original latticeBoltzmann method in our previous publications (Fei et al 2006;Fei and Hong 2007). The thermal effect influences the bubble transport significantly because the surface tension of a gas bubble depends on temperature.…”
Section: Introductionmentioning
confidence: 99%
“…2 Thermal lattice-Boltzmann method Details of a 2D, nine-velocity (D2Q9) lattice-Boltzmann model for a two-phase flow, including the treatment of boundary conditions, were explicitly described in our previous work (Fei et al 2006;Fei and Hong 2007). We derived the lattice-Boltzmann model from the physicallyoriented concept proposed by Shan and Chen (1993).…”
Section: Introductionmentioning
confidence: 99%